2022
DOI: 10.1111/sltb.12828
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical behavior therapy for adolescents (DBT‐A): Outcomes among sexual minorities at high risk for suicide

Abstract: The alarming rates and pervasiveness of suicidal and self‐destructive behaviors (e.g., non‐suicidal self‐injury) among young sexual minorities represent a major public health concern. We set out to examine whether an empirically driven treatment for suicide and self‐harm, dialectical behavior therapy for adolescents (DBT‐A), provides benefits for adolescents who identify as gay, lesbian, bisexual, or questioning (LGBQ). LGBQ adolescents (n = 16) were compared with non‐LGBQ peers (n = 23). Psychological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 74 publications
3
15
1
1
Order By: Relevance
“…In primary analyses, sexual minority participants did not differ from heterosexual participants in average levels or rates of change in suicide attempts, NSSI, global functioning, or hospitalization during DBT. This finding is consistent with past studies of DBT or DBT-based treatments (Beard et al, 2017; Poon et al, 2022). With regard to therapy more broadly, this finding is similar to a past study showing no differences in rates of change in anxiety and depression between sexual minority and heterosexual clients in college counseling centers (Lefevor et al, 2017) but differed from a past study finding worse outcomes on depression, anxiety, and functional impairment for lesbian and bisexual clients compared to heterosexual clients (Rimes et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In primary analyses, sexual minority participants did not differ from heterosexual participants in average levels or rates of change in suicide attempts, NSSI, global functioning, or hospitalization during DBT. This finding is consistent with past studies of DBT or DBT-based treatments (Beard et al, 2017; Poon et al, 2022). With regard to therapy more broadly, this finding is similar to a past study showing no differences in rates of change in anxiety and depression between sexual minority and heterosexual clients in college counseling centers (Lefevor et al, 2017) but differed from a past study finding worse outcomes on depression, anxiety, and functional impairment for lesbian and bisexual clients compared to heterosexual clients (Rimes et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Theoretical work suggests that the principles and structure of DBT may be well-suited to minoritized populations given its emphasis on the impact of invalidating environments on mental health and its core dialectic between acceptance and change (Chang & Cohen, 2022; Cohen et al, 2021; Pantalone et al, 2019; Pierson et al, 2021; Skerven et al, 2019; Sloan et al, 2017). Several studies have found that sexual minority people improved comparably to heterosexual people in various psychological and functional outcomes when participating in DBT for adolescents (Poon et al, 2022) and a cognitive behavioral therapy and DBT skills-based partial hospital program (Beard et al, 2017). However, bisexual people may have worse outcomes on suicidal and self-injurious thoughts compared to other sexual identity groups (Beard et al, 2017).…”
mentioning
confidence: 99%
“…Despite disproportionately high levels of depression, self-harm, and suicidal thoughts and behaviors in LGBTQIA+ youth relative to the general youth population, there remains a lack of suicide-specific mental health treatment and research addressing this disparity [ 7 ]. Preliminary research indicates that LGBTQIA+ youth who participate in adapted treatments demonstrate considerable clinical improvement after treatment [ 8 ] and that LGBTQIA+ youth describe the treatment as helpful in addressing their life stresses [ 9 ]. Given the disparities and the importance of intervening in serious mental health issues in adolescence and young adulthood, there is a critical need for more research on the efficacy of general and population-specific programming for LGBTQIA+ youth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This substance use intervention found that the tailored intervention led to greater reductions in substance use [ 24 ]. In 2 studies that adapted programming for LGBTQIA+ youth, youth had significantly reduced posttraumatic stress disorder symptoms [ 25 ], depression, and borderline symptoms after treatment [ 8 ]. Research on adults has similarly documented clinical improvement following adapted interventions [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Si bien el tratamiento de TDC se presenta de manera lineal y progresiva, las etapas del tratamiento con frecuencia se superponen y, a menudo, un paciente progresará en una etapa solo para retroceder nuevamente en otro momento (Koerner, 2012). Los estudios sobre los impactos de la TDC en población clínica se refieren principalmente a problemas de etapa 1 (Alba et al, 2022;Dunn et al, 2022;Hernández et al, 2022;Poon et al, 2022;Weinberg, 2022).…”
unclassified